Pembelajaran Pendidikan Agama Islam pada Anak Usia Dini - Jasuri (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2015)
Early age is a golden age for children, because at this age children grow and develop mentally and mentally. This period is also a period of character formation, personality and character. Early childhood is also the most important time for children, because it is a time of forming the main personality. Therefore it is important to give religious education early. The importance of inculcating religious values from an early age in order to create noble human beings. Islamic religious education is given to children from an early age through first introductions about God's creation of nature and everything in it. Then introduced worship, especially prayer, ablution, reading daily prayers. Also taught habituation that nuances of Islam in order to form moral morals.